Implementation of State Defense Policy in Border Area A Case Study in Natuna District, Indonesia - Mulyawan, Rahman; Sri Kartini, Dede (International Journal of Engineering and Technology, 2018)
Natuna Regency is a border area between the Republic of Indonesia with Malaysia and Vietnam, in this region there had been tension when China put Natuna into their sovereign territory. As a border area, Natuna has a strategic position, but defense development in this region is relatively left behind. This study focuses on the implementation of state defense policy in border area, especially in Natuna â€“ Indonesia. The method used in this study is qualitative research. Primary data in this research is the information form from informants, and secondary data obtained from various documents, journals, scientific papers, and others. From the research that has been done, it is known that the implementation of state defense policy in border area was not running well, based on the environmental aspect the stability condition in border area still weak, it is caused by the non-submission of the central defense authority by the central government to the Natuna Regency government which has special character as the border area between countries.Â Â Â